Simulation of a reversible SOFC with Aspen Plus. (13th April 2017) - Hauck, Maximilian; Herrmann, Stephan; Spliethoff, Hartmut
Abstract: A thermodynamic Aspen Plus simulation model for a reversible solid oxide fuel cell (RSOFC) is presented and evaluated. It is composed of an electrolysis and a fuel cell module. The latter is based on an existing non reversible SOFC model. The electrolysis model simulates water electrolysis as well as catalytic reactions of inlet gases. The model has been validated using data from literature. It has been found that the support layer on fuel electrode supported cells has to be treated differently in terms of diffusion than the active layer. Simulation results show that for the investigated cell parameters, the positive effect of adding CO2 to the steam feed on the electrolysis process is due to water–gas-shift reactions and not CO2 electrolysis. An analysis of outlet gas compositions in electrolysis mode showed that the assumption of the cell as an equilibrium reactor was justified. A parameter study has been conducted, showing that increasing the operation temperature and pressure can improve the overall performance, while changing the inlet gas compositions in general improves either fuel cell or electrolysis mode and deteriorates performance for the other mode. Graphical abstract: Highlights: An Aspen Plus model for a reversible solid oxide fuel cell is presented. Stack can be modelled as an equilibrium reactor. Overall cell performance increases with temperature. Optimal pressure depends on operation parameters.